Film forming systems for topical and transdermal drug delivery - Kashmira Kathe; Harsha Kathpalia (Elsevier, 2017)
Skin is considered as an important route of administration of drugs for both local and systemic effects. The effectiveness of topical therapy depends on the physicochemical properties of the drug and adherence of the patient to the treatment regimen as well as the system's ability to adhere to skin during the therapy so as to promote drug penetration through the skin barrier. Conventional formulations for topical and dermatological administration of drugs have certain limitations like poor adherence to skin, poor permeability and compromised patient compliance. For the treatment of diseases of body tissues and wounds, the drug has to be maintained at the site of treatment for an effective period of time. Topical film forming systems are such developing drug delivery systems meant for topical application to the skin, which adhere to the body, forming a thin transparent film and provide delivery of the active ingredients to the body tissue. These are intended for skin application as emollient or protective and for local action or transdermal penetration of medicament for systemic action. The transparency is an appreciable feature of this polymeric system which greatly influences the patient acceptance. In the current discussion, the film forming systems are described as a promising choice for topical and transdermal drug delivery. Further the various types of film forming systems (sprays/solutions, gels and emulsions) along with their evaluation parameters have also been reviewed.